CIT572 – Cyber Marketing July/August 2021 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 2021)
Second Semester Examination 2020/2021 Academic Session July/August 2021 CIT572 – Cyber Marketing (Pemasaran Siber) Duration : 2 hours (Masa : 2 jam)